1997
DOI: 10.1002/(sici)1098-1136(199709)21:1<22::aid-glia3>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic pathways for glucose in astrocytes

Abstract: Cultured astroglial cells are able to utilize the monosaccharides glucose, mannose, or fructose as well as the sugar alcohol sorbitol as energy fuel. Astroglial uptake of the aldoses is carrier‐mediated, whereas a non‐saturable transport mechanism is operating for fructose and sorbitol. The first metabolic step for all sugars, including fructose being generated by enzymatic oxidation of sorbitol, is phosphorylation by hexokinase. Besides glucose only mannose may serve as substrate for build‐up of astroglial gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
110
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(121 citation statements)
references
References 126 publications
4
110
0
3
Order By: Relevance
“…Brown, and B. Ransom, unpublished observations) but does not lead to glycogen formation in vitro (Wiesinger et al, 1997). As expected, nerves equilibrated for 60 min in 25 mM fructose had no change in glycogen content as compared with control (3.23 Ϯ 0.29 pmol of glycogen/ g of protein; n ϭ 6; p Ͼ 0.05 vs control); the significance of this observation is discussed later.…”
Section: Glycogen Content Of Ronsupporting
confidence: 63%
See 2 more Smart Citations
“…Brown, and B. Ransom, unpublished observations) but does not lead to glycogen formation in vitro (Wiesinger et al, 1997). As expected, nerves equilibrated for 60 min in 25 mM fructose had no change in glycogen content as compared with control (3.23 Ϯ 0.29 pmol of glycogen/ g of protein; n ϭ 6; p Ͼ 0.05 vs control); the significance of this observation is discussed later.…”
Section: Glycogen Content Of Ronsupporting
confidence: 63%
“…Fructose, like glucose, sustains the CAP, but it does not induce glycogen synthesis (Wiesinger et al, 1997) (see Fig. 3B).…”
Section: Glycogen Content and Axon Functionmentioning
confidence: 95%
See 1 more Smart Citation
“…Albeit at much lower concentrations, the brain also contains glycogen, which is primarily located in astrocytes (Wiesinger et al, 1997). Although accepted as the principal energy reserve in the CNS by many (Dringen et al, 1993;Swanson, 1992;Watanabe and Passonneau, 1973), the role of glycogen in the brain is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggested the involvement of brain glycogen in sleep cycle regulation (Kong et al, 2002;Petit et al, 2002). These changes in glycogen content may be brought about by a number of factors (Wiesinger et al, 1997) including hormones (Dringen and Hamprecht, 1992) and neurotransmitters (Hamai et al, 1999;Sorg and Magistretti, 1992;Swanson et al, 1990).…”
Section: Introductionmentioning
confidence: 99%